Kebijakan Umar ibn Abdul Aziz dalam Pemberantasan Korupsi - Ali, Muhammad Nasihudin (Mahesa Research Center (PT. Mahesa Global Publishing), 2020)
Bani Umayah is a dynasty founded by Muawiyah ibn Abu Sofyan. The name Umayyah is addressed to Umayyah ibn Abd Syams ibn Abdi Manaf, who was a Quraish figure during the era of ignorance. The reign of this dynasty experienced peace during the time of Umar ibn Abdul Aziz. He succeeded in uniting the warring groups. In addition, Umar ibn Abdul Aziz managed to eradicate the corruptors. This can be seen when Umar II fired offensive officials, one of which was the Governor of Khurasan, Yazid ibn Muhallab who committed evasion of provincial taxes. Umar II also replaced the second sermon at Friday prayers which previously denounced Ali ibn Abu Thali and his family, and replaced it with a verse of the Koran. The realization of peace and security of the people is the priority of Umar ibn Abdul Aziz rather than the expansion of power and the State. Research used by the author is to use library research, namely research whose data sources are taken from books and writings.